Teach them all to read catching the kids who fall through the cracks - McEwan-Adkins, Elaine K. 1941- (Thousand Oaks, Calif. Corwin Press, 2002)
"This insightful and practical book offers teachers at all levels the understanding and motivation they need to teach children to read-especially those students who need help the most."
Falling through the cracks -- Developing an action plan: read, focus, and reflect -- Putting the code pieces in place -- Fluency : the forgotten piece of the reading puzzle -- The meaning pieces: language, knowledge, and cognitive strategies -- Putting it all together: reading a lot -- Snapshots of success: classrooms and schools that work -- Putting the final piece in place : creating a pervasive and persuasive reading culture -- Phonics readers -- Brain-based reading: cognitive strategies to raise reading achievement -- Project PRIDE -- The "I do it, we do it, you do it" lesson sequence -- Checklists and forms to help you build a reading culture.
Keywords: Reading (Elementary); Language arts (Elementary)